Pediatr Respir J 2022
DOI: 10.56164/pediatrrespirj.2022.03
|View full text |Cite
|
Sign up to set email alerts
|

Post-lockdown respiratory virus epidemiology: a monocentric observational study

Abstract: During the 2020 lockdown and post-lockdown, we assisted in almost zeroing respiratory infections. This study aimed to describe the first epidemic of respiratory viruses after the easing of nonpharmaceutical interventions (NPIs) for the containment of COVID-19 in a pediatric cohort of patients.All children consecutively hospitalized because of a respiratory infection at our

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In a previous study, we documented the initial outbreak of respiratory viruses within a pediatric cohort consisting of 62 bronchiolitis patients, following the relaxation of nonpharmaceutical interventions (NPIs) designed to contain COVID‐19. Our study revealed emerging epidemiological trends during the 2021–2022 season 7 . The study continued into the following year as well and revealed that the prevalence of respiratory viruses, such as RSV, MPV, influenza A/B, and RV, increased after the relaxation of NPIs and in the second season compared to the first, there was a higher prevalence of these viruses 8 .…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…In a previous study, we documented the initial outbreak of respiratory viruses within a pediatric cohort consisting of 62 bronchiolitis patients, following the relaxation of nonpharmaceutical interventions (NPIs) designed to contain COVID‐19. Our study revealed emerging epidemiological trends during the 2021–2022 season 7 . The study continued into the following year as well and revealed that the prevalence of respiratory viruses, such as RSV, MPV, influenza A/B, and RV, increased after the relaxation of NPIs and in the second season compared to the first, there was a higher prevalence of these viruses 8 .…”
Section: Introductionmentioning
confidence: 51%
“…This finding further reinforces the notion that the severity of bronchiolitis caused by viruses other than RSV increased significantly, during the last epidemic. Bronchiolitis caused by viruses other than RSV appeared to be more severe in the 2022–2023 season compared to bronchiolitis caused by non‐RSV viruses in the 2021–2022 season 7 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These reductions in community infection rates have resulted in fewer hospitalizations and deaths associated with non-SARS-CoV-2 respiratory infections [ 18 ]. In a previous study, we described the first epidemic of respiratory viruses in a pediatric cohort of 123 patients after the easing of NPIs for the containment of COVID-19, reporting new epidemiological trends in the 2021–2022 season [ 19 ]. In the first post-pandemic epidemic, a multicenter Italian study demonstrated an early onset of the epidemiological curve for RSV and revealed that SARS-CoV-2 exhibited competitive pressure on other respiratory viruses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%